THE CONTRIBUTION OF LITERATURE TEACHING IN LEARNERâ€™S ABILITY TO RESPOND TEXT - Nur Antoni (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2017)
Abtract : Many discussions about the benefit of literary work and literature teaching lead the presence of this research. It appears to reveal the process of literature teaching in responding literature. This research explores about EFL learnerâ€™s ability in responding literary text whether it is directly or indirectly. This research, therefore, reveals the involvement of emotion, experience, and interest while responding text. This research also reveals the engagement between EFL learners and text based on some criteria which have stated above. Another problem is the way EFL learner respond text appropriately especially literary text. This research used case study because this research attempts to describe engagement between reader and literary work which pointed out by reader response. This research also wants to describe the contribution of literature teaching behind learnersâ€™ process in responding it. The researcher found contribution of literature teaching from learnersâ€™ involvement as respondents in this research, that is, learners involved their personal experience in responding text as aesthetic demand. This is the learning objective of â€œLiterary Work Analysisâ€ course and it means that the expected achievement in this course is achieved.Â Keywords : EFL, lietrature work, literature teaching, students responds.